2015
DOI: 10.1371/journal.pone.0138857
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Differences in Relative Gene Expression of Putative Central Appetite Regulators in Arctic Charr (Salvelinus alpinus) Do Not Reflect Its Annual Feeding Cycle

Abstract: The highly seasonal anadromous Arctic charr (Salvelinus alpinus) was used to investigate the possible involvement of altered gene expression of brain neuropeptides in seasonal appetite regulation. Pro-opiomelanocortin (POMCA1, POMCA2), Cocaine and amphetamine regulated transcript (CART), Agouti related Peptide (AgRP), Neuropeptide Y (NPY) and Melanocortin Receptor 4 (MC4-R) genes were examined. The function of centrally expressed Leptin (Lep) in fish remains unclear, so Lep (LepA1, LepA2) and Leptin Receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Instead of decreasing as fat stores are depleted (as predicted by adipostat), plasma leptin consistently increases with fasting in salmonids (108110) and flounder (111). Striberny et al (112) found no evidence that this change in circulating leptin titer was mediated by the CNS. Further, Arctic charr will spontaneously stop feeding in winter even while leptin titers are falling and even if presented with food (11), but will resume eating during the time of year when leptin concentrations are rising (113, 114).…”
Section: Leptin As An Adipostat: Lack Of Evidence In Fishesmentioning
confidence: 98%
See 1 more Smart Citation
“…Instead of decreasing as fat stores are depleted (as predicted by adipostat), plasma leptin consistently increases with fasting in salmonids (108110) and flounder (111). Striberny et al (112) found no evidence that this change in circulating leptin titer was mediated by the CNS. Further, Arctic charr will spontaneously stop feeding in winter even while leptin titers are falling and even if presented with food (11), but will resume eating during the time of year when leptin concentrations are rising (113, 114).…”
Section: Leptin As An Adipostat: Lack Of Evidence In Fishesmentioning
confidence: 98%
“…Although leptin is thought to drive the prehibernation anorexia of some, but not all hibernating mammals [reviewed in Ref. (117)], organisms with life histories that are distinctly seasonal (but not necessarily hibernating) may change their set point for leptin sensitivity to accommodate different levels of activity and food availability between seasons (97, 112, 118, 119); thus, an adipostat as described for rodents may not be adaptive for fishes.…”
Section: Leptin As An Adipostat: Lack Of Evidence In Fishesmentioning
confidence: 99%
“…In Arctic charr Salvelinus alpinus , non-feeding fish have higher brain AgRP expression levels than feeding fish (Striberny et al, 2015) and transgenic coho salmon Oncorhynchus kisutch , which display increased feeding, have higher brain AgRP1 levels of mRNA than wild-type fish (Kim et al, 2015), suggesting an orexigenic role for AgRP. However, in Atlantic salmon, AgRP-1 brain mRNA levels decrease after fasting (Murashita et al, 2009a) and increase after feeding (Valen et al, 2011), rather pointing to an anorexigenic role.…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Two CART isoforms have been identified in goldfish (Volkoff and Peter, 2001a) and common carp (Wan et al, 2012), and 4 in zebrafish (Akash et al, 2014) whereas, to date, only one form has been isolated for grass carp (Zhou et al, 2013; Liu et al, 2014), Characiformes [pirapitinga (serrasalmidae) (Volkoff, 2015a), pacu (serrasasalmidae) (Volkoff et al, 2017) and dourado (characidae) (Volkoff et al, 2016), red bellied piranha (serrasalmidae) (Volkoff, 2014a)], Salmoniformes [Atlantic salmon (Murashita et al, 2009a), rainbow trout (Figueiredo-Silva et al, 2012), Arctic charr (Striberny et al, 2015) and lake trout ( Salvelinus namaycush ) (Volkoff et al, 2007)], Siluriformes (channel catfish Kobayashi et al, 2008), Gadiformes (Atlantic cod Kehoe and Volkoff, 2007), Perciformes (cunner Babichuk and Volkoff, 2013), winter flounder (MacDonald and Volkoff, 2009a) and Atlantic halibut ( Hippoglossus hippoglossus ) (Gomes et al, 2015) (Pleuronectiformes), venomous toadfish Thalassophryne nattereri (Batrachoidiforme) (Magalhaes et al, 2006), rainbow smelt ( Osmerus mordax ) (Osmeriforme), pufferfishes ( Takifugu rubripes and Tetraodon nigroviridis , Tetraodontiforme) and stickleback Gasterosteus aculeatus (Gasterosteiforme) (cited in Murashita et al, 2009a). However, six forms of CART have been identified in the medaka (Beloniforme) (Murashita and Kurokawa, 2011) and seven forms in Senegalese sole Solea senegalensis (Pleuronectiforme), the highest number of CART genes reported to date in a vertebrate species (Bonacic et al, 2015).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
See 1 more Smart Citation